Yeast communities and other microbial components in tropical peat swamp forests - Khunnamwong, Pannida; Limtong, Savitree (Agriculture and Natural Resources, 2024)
Tropical peat swamp forests (PSFs), also known as peatlands, coexist with swamp forests, and form a unique ecosystem that serves as an important global carbon reservoir. Climate change can have major effects on microbial communities in this ecosystem. To understand these effects, it is necessary to know the composition of their microbial diversity. Therefore, this study reviewed many articles related to PSFs and their microbial communities and then analyzed and summarized microbial communities and, specifically, yeast communities. This review article has provided a current list of yeasts found in PSFs. In addition, differences in yeast composition were found in these communities, not among the different types of PSF, but also in PSFs of the same type. These differences could arise, not only from using different investigation techniques, but also from differences in various environmental factors in the PSFs that were studied. This review article should be useful for not only researchers working specifically on climate change effects on microbial communities in the PSFs, but also for researchers working generally on microbial communities in other ecosystems.